1987
DOI: 10.1136/oem.44.9.638
|View full text |Cite
|
Sign up to set email alerts
|

Pentachlorophenol and the peripheral nervous system: a longitudinal study in exposed workers.

Abstract: A longitudinal study was performed to examine whether chronic occupational exposure to pentachlorophenol (PCP) or its compounds causes measurable alterations in the conduction velocity in peripheral nerves as an "adverse effect." In total, the results of nerve conduction velocity (NCV) determinations in 1980 and 1984 in 10 subjects (7 men, 3 women) who had been exposed for an average of 16 years (range 4-24) were available. The concentrations of PCP in the air at the workplace varied between 0 3 and 180 yg/m3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
1
1
Order By: Relevance
“…The urinary PCP concentrations in our study were in the range found in the US general population (median 1.2 mg/g creatinine) [Hill et al, 1995b] as well as below the levels found in the early 90s in the Germany general population (2.15 mg/g creatinine) [Angerer et al, 1992b]. Therefore, the exposure levels observed in the harbor workers under study are within levels from the general population and well below levels found in earlier studies among subjects with workplace exposure to PCP [Triebig et al, 1987;Pekari et al, 1991].…”
Section: Discussioncontrasting
confidence: 61%
“…The urinary PCP concentrations in our study were in the range found in the US general population (median 1.2 mg/g creatinine) [Hill et al, 1995b] as well as below the levels found in the early 90s in the Germany general population (2.15 mg/g creatinine) [Angerer et al, 1992b]. Therefore, the exposure levels observed in the harbor workers under study are within levels from the general population and well below levels found in earlier studies among subjects with workplace exposure to PCP [Triebig et al, 1987;Pekari et al, 1991].…”
Section: Discussioncontrasting
confidence: 61%
“…The Material Safety Data Sheets for pentachlorophenol and pentabromophenol note their aquatic toxicity and moderate bioconcentration factors as up to 10 4 for PCP and 10 2 for PBP [ 7 , 8 ]. However, the brominated flame retardants are similarly documented regarding their human health concerns as endocrine disruptors [ 9 ], and the chlorinated phenols are documented as affecting the nervous system [ 10 ], and with long exposure potentially causing cancer [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%